Kinetic and crystallographic studies on deacetoxycephalosporin C synthase (DAOCS). - Lee, H; Lloyd, MD; Harlos, K; Clifton, I; Baldwin, J; Schofield, C (2001)
Deacetoxycephalosporin C synthase (DAOCS) is an iron(II) and 2-oxoglutarate-dependent oxygenase that catalyzes the conversion of penicillin N to deacetoxycephalosporin C, the committed step in the biosynthesis of cephalosporin antibiotics. The crystal structure of DAOCS revealed that the C terminus of one molecule is inserted into the active site of its neighbor in a cyclical fashion within a trimeric unit. This arrangement has hindered the generation of crystalline enzyme-substrate complexes. Therefore, we constructed a series of DAOCS mutants with modified C termini. Oxidation of 2-oxoglutarate was significantly uncoupled from oxidation of the penicillin substrate in certain truncated mutants. The extent of uncoupling varied with the number of residues deleted and the penicillin substrate used. Crystal structures were determined for the DeltaR306 mutant complexed with iron(II) and 2-oxoglutarate (to 2.10 A) and the DeltaR306A mutant complexed with iron(II), succinate and unhydrated carbon dioxide (to 1.96 A). The latter may mimic a product complex, and supports proposals for a metal-bound CO(2) intermediate during catalysis.